PainVet: escala digital de valoración del dolor en perros. - Castillo Hidalgo, Edy Paul; Pillaga Gaona, Christian; Rubio, Pablo; Alvarado, Juan; Maldonado, Manuel (Universidad Técnica de Machala, 2021)
With the exponential growth of smartphone devices, several applications have been developed in veterinary science that have contributed to facilitate the access to information in different areas, including pain assessment, which has been a constant concern of animal health professionals. The objective of this work was to develop and implement a digital App based on the Melbourne and Glasgow modified scale, rising data for the Android operating system and as result obtain a digital scale, with a score of 27 points, based on 5, levels of pain, and a PDF exporter. For the verification of this application, all the dependent variables used by the Melbourne and Glasgow scale were quantified, in two methods: manual and digital and then compared. 87 post-surgical dogs were used, of which, 43 patients were Manual (printed scale) with a total of 208 observations at different times, while 44 patients were tested with PainVet, with a total of 197 observations, defining a confidence interval (P<0.05) and a T-test for compare de distribution of results. This led us to conclude that PainVet is a useful tool that allows us to assess and record levels of post-surgical pain in canines. In addition, it was possible to observe that patients with post-surgical pain most frequently present mydriasis, salivation, vomiting, and changes in their mental state, signs that become key in the assessment of post-surgical pain in dogs
Con el crecimiento exponencial del uso de dispositivos móviles inteligentes, se han desarrollado varias aplicaciones en medicina veterinaria que han contribuido a facilitar el acceso a la información en diferentes ámbitos, en los cuales se incluyen la evaluación del dolor, el cual ha sido una preocupación constante de los profesionales de la salud animal. En el presente trabajo se planteó como objetivo desarrollar e implementar una App digital basados en la escala de Melbourne y Glasgow modificada, desarrollando una base de datos para el sistema operativo Android, obteniendo una escala digital, con un score de 27 puntos, 5 niveles de dolor, y un exportador PDF. Para la verificación de esta aplicación se procedió a cuantificar las variables dependientes que utiliza la escala de Melbourne y Glasgow, evaluando el dolor postquirúrgico en un total de 113 perros, de los cuales, en 43 pacientes se realizaron 208 observaciones en diferentes tiempos por medio de la escala impresa, en tanto que mediante PainVet se observaron y valoraron 70 pacientes, con un total de 197 observaciones, definiendo un intervalo de confianza (P<0.05). Lo que nos llevó a concluir que PainVet es una herramienta útil, que permite valorar y registrar los niveles de dolor posquirúrgico en caninos; de igual forma se pudo observar que los pacientes con dolor posquirúrgico presentan con mayor frecuencia midriasis, salivación, vómitos y cambios de su estado mental, signos que se convierten en claves en la valoración del dolor posquirúrgico en perros.
Keywords: DOLOR; EVALUACIÓN; PERROS; APP; SMARTPHONE